An Experimental Study on Hybrid Noncompression CF Bracing and GF Sheet Wrapping Reinforcement Method to Restore Damaged RC Structures - Kang Seok Lee (Shock and Vibration)
We describe a novel technique for restoration of reinforced concrete (RC) structures that have sustained damage during an earthquake. The reinforcement scheme described here is a hybrid seismic retrofitting technique that combines noncompression X-bracing using CF with externally bonded GF sheets to strengthen RC structures that have sustained damage following an earthquake. The GF sheet is used to improve the ductility of columns, and the noncompression CF X-bracing system, which consists of CF bracing and anchors to replace the conventional steel bracing and bolt connections, is used to increase the lateral strength of the framing system. We report seismic restoration capacity, which enables reuse of the damaged RC frames via the hybrid CF X-bracing and GF sheet wrapping system. Cyclic loading tests were carried out to investigate hysteresis of the lateral load-drift relations, as well as the ductility. The GF sheet significantly improved the ductility of columns, resulting in a change in failure mode. The strengthening effect of conventional CF sheets used in columns is not sufficient with respect to lateral strength and stiffness. However, this study results in a significant increase in the strength of the structure due to the use of CF X-bracing and inhibited buckling failure of the bracing. This result can be exploited to develop guidelines for the application of the reinforcement system to restore damaged RC structures.